Foot clearance measurement - Chia, Roy Hao Wen (2017)
Foot clearance measurement has been helpful in the rehabilitation section of the medical field. With many different devices out in the market such as motion camera, ultra-wide band sensors, accelerometers and etc. this papers looks towards ultrasonic sensors to obtain accurate data for foot clearance measurement.